Depth of invasion in early oral cancers- is it an independent prognostic factor?. Issue 8 (August 2021) - D'Cruz, Anil K.; Dhar, Harsh; Vaish, Richa; Hawaldar, Rohini; Gupta, Sudeep; Pantvaidya, Gouri; Chaukar, Devendra; Chaturvedi, Pankaj; Pai, Prathamesh; Deshmukh, Anuja; Kane, Shubhada; Nair, Deepa; et al.
Abstract: Introduction: Depth of invasion (DOI) has been incorporated into oral cancer staging. Increasing DOI is known to be associated with an increased propensity to neck metastasis and adverse tumor factors and hence may not be an independent prognosticator but a surrogate for a biologically aggressive tumor. Methods: 570 patients, median follow up 79.01 months from a previously reported randomized trial (NCT00193765) designed to establish appropriate neck treatment [elective neck dissection (END) vs therapeutic neck dissection (TND)] in clinically node-negative early oral cancers were restaged (nT) according to AJCC TNM 8th edition. Overall survival (OS) was estimated for the entire cohort, END, and TND arms. Multivariate analysis performed for stratification and prognostic factors, and interaction term between revised T-stage and neck treatment, for tumours with DOI≤10mm. Presence of adverse factors was compared between nT3 (DOI>10 mm) and those with DOI≤10 mm. Results: Stage migration occurred in 44.38% of patients. 5-Year OS was nT1-79%, nT2-69.4% and nT3-53.8%, (p < 0.001). In TND arm 5-year OS was nT1-81.1% versus nT2-65%, p = 0.004, while that in END arm was nT1 -76.9% versus nT2 -73.7%, p = 0.73. There was a significant interaction between T stage and neck treatment (p = 0.03). T3 tumors (>10 mm) were associated with a higher proportion of adverse factors (occult nodal metastasis, p = 0.035; LVE/PNI, p = 0.001). Conclusion: Elective neck treatment negates the prognostic impact of DOI for early oral cancers (T1/T2 DOI≤10 mm). T3 tumors with DOI>10 mm have a higher association with other adverse risk factors resulting in poorer outcomes in spite of elective neck dissection.